Дослідження зчеплення скляних пластин між собою за дії статичного навантаження - Ткач, Р. О.; Демчина, Б. Г.; Сурмай, М. І.; Вознюк, Л. І.; Нємєц, Я.; Tkach, Roman; Demchyna, Bohdan; Surmai, Mykhaylo; Vozniuk, Leonid; Niemiec, Janusz (Видавництво Львівської політехніки, 2019)
Слабким місцем будь-якої конструкції завжди є вузол з’єднання елементів. У статті наведено результати дослідження зчеплення скляних пластин, які з’єднані між собою по всій поверхні за допомогою клеючих матеріалів та виготовлених за технологією триплексування, за дії статичного навантаження. Встановлено несучу здатність та деформативність таких з’єднань. Для проведення досліджень спроєктовано, виготовлено та випробувано шість серій дослідних зразків. Дослідні зразки складалися з трьох скляних пластин, товщина кожної 10 мм, з’єднаних між собою за допомогою технології триплексування та різних клеючих матеріалів. Розроблено програму експериментальних досліджень. На основі отриманих результатів проаналізовано роботу зчеплення скляних пластин та побудовано усереднений графік залежності деформацій зсуву та дотичних напружень τ=N/A для серій дослідних зразків.

The weak point of any structure is always the elements junction node. This article presents the results of a study of the adhesion of glass plates interconnected over the entire surface by means of adhesive materials and triplex technology under the action of static loading. The bearing capacity and deformability of such joints was established. For the research purposes there were designed, manufactured and tested six series of prototypes. The prototypes consisted of three glass plates, each 10 mm thick, interconnected by means of triplex technology and various adhesive materials. Before bonding, the glass plates of the prototypes of I–V series were cleaned of dirt and degreased. The adhesive was applied to the entire surface of one plate. Then, the glass plates were firmly interconnected with the help of the vise and held for 5–10 minutes. The curing time depended on the adhesive materials. The curing of the glue of the samples of the fourth and fifth series was done under the rays of an ultraviolet lamp. The plates of the sixth series prototypes were interconnected by triplex technology, where EVASAFE polymer film (Bridgestone, Japan) was inserted between the plates and the prototypes were heated to 130 ºC and held for 30 minutes. An experimental research program was developed. The test rig consisted of a stand for static structural strength tests. The external load N was applied by means of a hydraulic jack and was performed step by step. The magnitude of the load was 1.0 kN and was monitored using a DOSM-3-50U dynamometer for the I–V series prototypes and a ring dynamometer for the VI series prototypes until the complete destruction of the prototype. At each load stage a 10 min exposure was performed followed by gauge reading. On the basis of the obtained results, an analysis of glass plates adhesion was performed and an averaged dependency graph of shear deformations and tangent stresses τ = N / A for the series of the prototypes was constructed.
A study of mutual adhesion of glass plates under static loading
Keywords: шари скла; триплекс; дослідний зразок; скляні пластини; glass layers; triplex; prototype; glass plates